Identification of inhibitors from a functional food-based plant Perillae Folium against hyperuricemia via metabolomics profiling, network pharmacology and all-atom molecular dynamics simulations - Wu, Chuanghai; Wong, Ann Rann; Chen, Qinghong; Yang, Shuxuan; Chen, Meilin; Sun, Xiaomin; Zhou, Lin; Liu, Yanyan; Yang, Angela Wei Hong; Bi, Jianlu; Hung, Andrew; Li, Hong; et al. (Frontiers in Endocrinology, 2024)
Hyperuricemia (HUA) is a metabolic disorder caused by purine metabolism dysfunction in which the increasing purine levels can be partially attributed to seafood consumption. Perilla Folium (PF), a widely used plant in functional food, has been historically used to mitigate seafood-induced diseases. However, its efficacy against HUA and the underlying mechanism remains unclear. Here, we employed a network pharmacology analysis to identify candidate targets and explored potential mechanisms involved in PF treating HUA. We obtained 8200 predicted binding results through supercomputeraided molecular docking calculations between 328 herbal compounds and 25 targets, and xanthine dehydrogenase (XDH) exhibited the highest average binding affinity. We built a network comprised of core compounds and hub targets based on docking results to display their biological interactions. We also compared the structures of 328 ligands with mainstream XDH inhibitors and conducted a cluster analysis of compound structures. We screened out five promising ligands (scutellarein, benzyl alpha-D-mannopyranoside, elemol, diisobutyl phthalate, and (3R)-hydroxy-beta-ionone) and performed molecular dynamics (MD) simulations up to 50 ns for XDH complexed to them. The scutellarein-XDH complex exhibited the most satisfactory stability. Furthermore, a text-mining study provided laboratory evidence of scutellarein's function while an untargeted metabolomics analysis confirmed the its presence of it. Extending MD simulations to 200 ns further examined indicated the sustained impact of scutellarein on XDH structure. Overall, our study provides a computational and biomedical basis for PF treating HUA and fully elucidates scutellarein's great potential as an XDH inhibitor at the molecular level, holding promise for future drug design and development.